Use of whole blood deployment programs for mass casualty incidents: South Texas experience in regional response and preparedness. Issue 6 (31st December 2022) - Ciaraglia, Angelo; Brigmon, Erika; Braverman, Maxwell; Kidd, Emily; Winckler, CJ; Epley, Eric; Flores, Jose; Barry, John; DeLeon, Daniel; Waltman, Elizabeth; Eastridge, Brian; Stewart, Ronald; et al.
Abstract : Brief report on an institutional experience with the first ever mass deployment of whole blood to a mass casualty incident for the Uvalde, TX school shooting. Abstract : INTRODUCTION: Firearm-related deaths have become the leading cause of death in adolescents and children. Since the Sutherland Springs, TX mass casualty incident (MCI), the Southwest Texas Regional Advisory Council for trauma instituted a prehospital whole blood (WB) program and blood deployment program for MCIs. METHODS: The program was adopted statewide by the Texas Emergency Medical Task Force, of which Southwest Texas Regional Advisory Council is the lead for Emergency Medical Task Force 8. The recent active shooter MCI in Uvalde, TX was the first time the MCI blood deployment program had been used. To our knowledge, no other similar programs exist in this or any other country. RESULTS: On May 24, 2022, 19 children and 2 adults were killed at an MCI in Uvalde, TX. The MCI WB deployment protocol was initiated, and South Texas Blood and Tissue Center prepared 15 U of low-titer O-positive whole blood and 10 U of leukoreduced O packed cells. The deployed blood arrived at Uvalde Memorial Hospital within 67 minutes. One of the pediatric patients sustained multiple gunshots to the chest and extremities. The child was hypotensive and received 2 U of leukoreduced O packed cells, one at the initial hospital and another during transport. On arrival, the patient required 2 U of low-titer O-positive whole blood and underwent a successful hemorrhage control operation. The remaining blood was returned to South Texas Blood and Tissue Center for distribution. CONCLUSION: Multiple studies have shown the association of early blood product resuscitation and improved mortality, with WB being the ideal resuscitative product for many. The ongoing efforts in South Texas serve as a model for development of similar programs throughout the country to reduce preventable deaths. This event represents the first ever successful deployment of WB to the site of an MCI related to a school shooting in the modern era. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level V. Abstract :